Clinical presentation and outcome in a series of 88 patients with the cblC defect. Issue 5 (6th March 2014) - Fischer, Sabine; Huemer, Martina; Baumgartner, Matthias; Deodato, Federica; Ballhausen, Diana; Boneh, Avihu; Burlina, Alberto B.; Cerone, Roberto; Garcia, Paula; Gökçay, Gülden; Grünewald, Stephanie; Häberle, Johannes; et al.
Abstract: The cblC defect is the most common inborn error of vitamin B12 metabolism. Despite therapeutic measures, the long‐term outcome is often unsatisfactory. This retrospective multicentre study evaluates clinical, biochemical and genetic findings in 88 cblC patients. The questionnaire designed for the study evaluates clinical and biochemical features at both initial presentation and during follow up. Also the development of severity scores allows investigation of individual disease load, statistical evaluation of parameters between the different age of presentation groups, as well as a search for correlations between clinical endpoints and potential modifying factors. Results: No major differences were found between neonatal and early onset patients so that these groups were combined as an infantile‐onset group representing 88 % of all cases. Hypotonia, lethargy, feeding problems and developmental delay were predominant in this group, while late‐onset patients frequently presented with psychiatric/behaviour problems and myelopathy. Plasma total homocysteine was higher and methionine lower in infantile‐onset patients. Plasma methionine levels correlated with "overall impression" as judged by treating physicians. Physician's impression of patient's well‐being correlated with assessed disease load. We confirmed the association between homozygosity for the c.271dupA mutation and infantile‐onset but not between homozygosity for c.394C>T and late‐onset. Patients were treated with parenteral hydroxocobalamin, betaine, folate/folinic acid and carnitine resulting in improvement of biochemical abnormalities, non‐neurological signs and mortality. However the long‐term neurological and ophthalmological outcome is not significantly influenced. In summary the survey points to the need for prospective studies in a large cohort using agreed treatment modalities and monitoring criteria.